MEMAHAMI STRATEGI PEMBINAAAN ROHANI UNTUK WARGA GEREJA: MEMBANGUN IMAN DAN KARAKTER JEMAAT - Ofertiaman Zai; Arde Justitia Zebua (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to understand effective spiritual training strategies for church members in building the faith and character of the congregation. Using a qualitative approach with a case study method, this study utilizes a literature review to explore theories related to theological teaching and community development. Data were obtained through in-depth interviews with church leaders and congregation members, as well as participant observation during worship and small group activities. Thematic analysis was conducted to identify practices that support spiritual growth. The results of the study indicate that in-depth theological teaching, supported by a solid community and involvement in service, contributes significantly to the formation of strong faith and character. This study is expected to contribute to the development of better spiritual development strategies in the church.